On Measuring the Nearness of Near-Moneys: Comment - Lee, Tong Hun (American Economic Review, 1972)
In a recent paper published in this Review, V. K. Chettv developed an interesting method of estimating the substitution parameters between liquid assets and found that commercial bank time and savings deposits, mutual savings bank deposits, and savings and loan association shares (T,MS, and SL hereafter) rank in the descending order of imnportance as near-moneys. While Chetty suggested inclusion of these nearmoneys in the definition of money, he argued that since T are closer substitutes for money than are SL, Milton Friedman's definition of money including T but not SL is also justified. Indeed, Friedman and Anna Schwartz (1970, p. 188) subsequently claimed that his definition of money is confirmed by Chetty's results. Chetty's finding, however, depends critically on the incorporation in his analysis of pre-1951 observations which do not reflect an important institutional change that occured in 1951 affecting the substitution parameters. Omitting such observations but using the same method, this paper will show that SL are closer substitutes for money than are T. Although this result does not affect the basic methodological contribution made by Chetty, it reverses his empirical finding. While I will not argue for including SL in the definition of money for the reasons discussed later, the present finding has an important implication for rejecting Friedman's concept of money now widely accepted in monetary analyses. Chetty employed 1945-66 annual timeseries observations for his analysis, but the analvsis should have been confined to a period after 1950. In the fall of 1950, the insurance provision of the Federal Savings and Loan Insurance Corporation was made more liberal than before in the event of default of an insured savings and loan association. As noted by Friedman and Schwartz (1963, p. 669), this provision in fact became identical to that governing the Federal Deposit Insurance Corporation. It is, therefore, quite reasonable to expect that the nearness of SL to money has increased since 1951. Indeed, there is evidence (see G. K. Kardouche, Lee (1966)) showing that the substitutability of SL for money has shifted due to the institutional change cited here. In addition, the post-1950 data pertain to the period of revival of monetary policy since the 1951 Accord and the analysis of substitution effects in a policy context should be directed to such data. With the 1951-66 data, Chetty's estimating equations are recomputed. Since there was evidence of autocorrelation among the least squares residuals, the equations are reestimated to remove autocorrelation by using Phoebus DhrvNmes' method with the following results.: 1 (1) log T = .0180 38.81 log (.061) (2.94) 1 + rT